Perancangan Clinical Decision Support System (CDSS) untuk Drug Drug Interaction (DDI) pada e-Prescription - Resia Perwirani; Ika Puspitasari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Not all drugs side-effect that occur can be avoided, but those caused by drug-drug interactions (DDI) are among the most likely to be prevented and managed due to their predictability. The increasing number of drugs co-prescribed, affects the potential for drug interactions exponentially. Clinical Decision Support System (CDSS) is a promising strategy to prevent patient safety risks caused by drug interactions. This study aims to design a CDSS for DDI on e-Prescription. This research is qualitative study with action research design. The research was carried out at Digital Health Innovation Studio (DHIS) UGM, and at Budi Rahayu Hospital Magelang with the implementation time November 2021 - April 2022. Data collection for user needs analysis was carried out by interviewing management, doctors and pharmacists at the hospital, and also pharmacologists. Design and development of CDSS-DDI was executed in collaboration with DHIS UGM programmers. The evaluation was done by interviews and a System Usability Scale (SUS) questionnaire filled in by 17 system-related users. CDSS-DDI successfully developed according to user needs, it can be accessed by doctors and pharmacy units. The drug interaction warning display pop-up appears on one screen in the e-Prescription menu with a description of drug interactions in Bahasa. Drug interaction data refers to the National Drug Information Center (PIONas) which is managed by the POM. CDSS-DDI then implemented in hospital after going through socialization. Based on evaluation with SUS data processing tools, the CDSS-DDI received a score of 83 in the acceptable category and excellent rating. Based on results of evaluation interviews, CDSS for DDI is considered to have been successfully developed with the principle of user centered design and optimally efficient to help improve the quality of patient care.